KRISIS EKONOMI DALAM PERSPEKTIF EKONOMI ISLAM PEMBERDAYAAN EKONOMI UMAT DARI PERSPEKTIF ISLAM (Harmoni, 2013)
Economic experts have concluded that the fundamental economic fragility is a major cause of the economic crisis. Deficit balance of payments, foreign debt burden swells - particularly short-term debt, inefficient investments, and many other economic indicators has been active in inviting the emergence of the economic crisis. When in fact the main cause is none other than the error due to the economic system and greediness. This paper tries to highlight the factors that cause the economic crisis of the religious aspects, economic ethical aspects, behavioral economic agents and other qualitative aspects.
Keywords: kerapuhan fundamental ekonomi; fundamental economic fragility; aspek keagamaan; religious aspect; aspek etika ekonomi; economic ethical aspects; Umat; Islam